The Effect of Advertising, Price and Product Quality on Consumer Satisfaction at the Zona Temu Cafe in Palopo City - Tagan, Yapet; Ramadan, Ramadan; Inem, Inem; Nurjannah, Nurjannah; Nasruddin, Nasruddin (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Problems in marketing have a close relationship with advertising, price and product quality itself. These problems often occur along with the emergence of various company concepts that have the same marketing strategy. Zona Temu Kafe Kota Palopo is a cafe engaged in F&B that sells food and drinks. The purpose of this study was to determine the effect of advertising, price and product quality on customer satisfaction at the Zona Kafe Palopo Palopo City .This study uses a descriptive analysis method using a Likert scale with 50 respondents who are then processed using the help of SPSS version 20. From this study it was found that based on the results of the research conducted, it was found that the variable advertising (X1), price (X2), product quality (X3) together had a positive and significant effect on the variable customer satisfaction (Y). The conclusion obtained is that 73.3% of customer satisfaction is influenced and can be explained by the variables of advertising, price, and product quality while the remaining 26.7% is explained by other variables not examined in this study.